X-ray phase-contrast 3D virtual histology characterises complex tissue architecture in colorectal cancer - Svetlove, Angelika; Griebel, Titus; Albers, Jonas; D’Amico, Lorenzo; Nolte, Philipp; Tromba, Giuliana; Bohnenberger, Hanibal; Alves, Frauke; Dullin, Christian (Frontiers in Gastroenterology, 2023)
Precise morphological analysis of tumour tissue samples is crucial for accurate diagnosis and staging of colorectal cancer (CRC) and remains limited by the 2D nature of conventional histology. Our aim is to offer a 3D representation of tissue samples by means of x-ray-based imaging to facilitate the evaluation of clinically relevant features in cancer tissue that is currently subject to various restrictions. In this study, we show that propagation based synchrotron micro computed tomography (SRµCT) is suitable for standard formalin-fixed-paraffin-embedded tissue of CRC patients to generate 3D tumour volumes with a 2 µm voxel and sufficient contrast for virtual histology. We demonstrate that using an existing registration pipeline, a 2D histological 1 Svetlove & Griebel et al.hematoxylin-eosin slice can be placed in the context of the 3D µCT volume. The precisely registered histological section can then be used as a 'seed point' for segmentation and depiction of major histological features. This approach allows for a more comprehensive understanding of tumour organisation in space with respect to other structures such as vessels, fat and lymph nodes and has the potential to improve patient prognostic outcomes.